Differential Neuronal Susceptibility and Apoptosis in Congenital Zika Virus Infection. (4th October 2017) - Ho, Cheng-Ying; Ames, Heather; Tipton, Ashley; Vezina, Gilbert; Liu, Judy; Scafidi, Joseph; Torii, Masaaki; Rodriguez, Fausto; duPlessis, Adre; DeBiasi, Roberta
Abstract: Background: Zika virus (ZIKV) infection during pregnancy may result in severe neurologic injury to the fetus. The mechanisms by which ZIKV injures fetal brain are not fully characterized. Although cell culture and animal models shed valuable insight into pathogenesis, they do not fully recapitulate human disease. Methods: To characterize the mechanism of ZIKV-induced human brain injury, we performed immunolabeling on brain tissue from a 20-week fetus with intrauterine ZIKV infection. Formalin-fixed sections of brain tissue were co-immunostained with ZIKV envelope antibody, as well as neuronal and non-neuronal lineage cell markers to assess infection within populations. Apoptosis was assessed by quantifying activated caspase 3 -positive staining cells. Minimum 3–5 random microscopic fields per brain region were photographed and quantified in an automated fashion using the ImageJ Cell Counter plug-in. GraphPad Prism and Microsoft Excel software were used for data analysis. Results: ZIKV demonstrated a wide range of neuronal and non-neuronal tropism. However, infection rate was highest in Tbr2+ - Intermediate Progenitor Cells (IPC; 81.4±12%) and DCX+ Immature Neurons (IN; 51.5±13.9%), followed by SOX2+/ Nestin+ Neural Precursor Cells (NPC; 26.6±13.4%). NeuN+ Mature Neurons had the lowest frequency of infection (MN; 10.0±7.0 %) (Figure). Apoptosis was observed in both infected and uninfected bystander cortical neurons. A high infection frequency was also observed in non-neuronal cells (astrocytes, microglia, macrophages, lymphocytes). Conclusion: Our study provides valuable insights into ZIKV pathogenesis in the fetus; it is the first to demonstrate differential infectivity/susceptibility of neuronal lineage cells to ZIKV, and evidence of apoptosis in and around these cells. The high frequency of ZIKV+ IPC and IN implies that that infection can be supported until the immature stage of neuronal differentiation. The resistance of mature neurons to ZIKV infection may also explain why ZIKV infection in the third trimester poses less risk of microcephaly in infants. The high infection rate of non-neuronal cells also suggests potential contribution of immune-mediated mechanisms of brain injury in the setting of congenital ZIKV infection. Disclosures: All authors: No reported disclosures.